Emerging illegal wildlife trade issues: a global horizon scan - Esmail, N; Wintle, B; 't Sas-Rolfes, M; Athanas, A; Beale, CM; Bending, Z; Dai, R; Fabiniyi, M; Gluszek, S; Haenlein, C; Harrington, L; Hinsley, A; et al. (Wiley Open Access, 2020)
Illegal wildlife trade is gaining prominence as a threat to biodiversity, but addressing it remains challenging. To help inform proactive policy responses in the face of uncertainty, in 2018 we conducted a horizon scan of significant emerging issues. We built upon existing iterative horizon scanning methods, using an open and global participatory approach to evaluate and rank issues from a diverse range of sources. Prioritised issues related to three themes: developments in biological, information and financial technologies; changing trends in demand and information; and socio-economic and geopolitical shifts and influences. The issues covered areas ranging from changing demographic and economic factors to innovations in technology and communications that affect IWT markets globally; the top three issues related to China, illustrating its vital role in tackling emerging threats. This analysis can support national governments, international bodies, researchers and non-governmental organisations as they develop strategies for addressing the illegal wildlife trade.